Penguatan Regulasi Internal Sebagai Bentuk Implementasi MACa Dalam Peningkatan Kinerja Koperasi - Anggraeni, Fadjar Setiyo; Endang Sarwiningsih, Setyawulan; Umi, Farichah; Arifa, Khairunisa (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Sultan Agung Syariah Consumer Cooperative (KOPMENSA) faces challenges in enhancing its performance due to ineffective management and insufficient revenue sources. Strengthening internal regulations is deemed crucial to address these issues, focusing on the formulation of standard operating procedures (SOPs) and the selection of competent leaders. The community service method involved assistance in administrative improvements and entrepreneurship training for members. The results indicate that the implementation of sound regulations and adaptive leadership can significantly enhance KOPMENSA’s performance. These findings underscore the importance of developing internal regulations and selecting the right managers for the sustainability and effectiveness of the cooperative